Treated wastewater reuse in South Africa: Overview, potential and challenges - Adewumi, J.R.; Ilemobade, A.A.; Van Zyl, J.E. (Resources, conservation and recycling, 2010)
Many communities in South Africa struggle to access reliable and adequate quantities of potable water for diverse water requirements. This is against the backdrop of decreasing freshwater availability and increasing water demands. Currently, interest in the reuse of wastewater for non-drinking water requirements is increasing. This paper therefore provides an overview of the South African water resources situation and wastewater 1 1 Wastewater refers to domestic, institutional, and industrial liquid waste products collected through networks of pipes (sewers) into treatment plant. generation in order to put the need for wastewater reuse into perspective. Potential for broader implementation and parameters influencing wastewater reuse based on local attitudes and experience were discussed with recommendations to facilitate broader implementation of wastewater reuse. This paper concludes that significant potential exists for implementing wastewater reuse for large non-drinking applications (e.g. landscape irrigation and industrial processes) in arid areas of South Africa especially Western Cape Province. Parameters highlighted from local attitudes and experience to influence broader implementation in addition to aridity include distance from source, retrofitting versus new installations, quantity of reuse, tariffs, source quality, public health, willingness, public trust and knowledge, and regulations and guidelines for reuse. Prior to implementation, it is recommended that these parameters be addressed.